(untitled) (Research, Society and Development, 2021)
Patients’ knowledge and awareness of their disease and medication (health literacy) are essential to ensure treatment effectiveness. This work analyzed the health literacy (HL) level of users of the Brazilian Unified Health System (SUS) in Diadema city (SP) and its consequences concerning the rational use of prescribed medication. A total of 1,121 SUS users were interviewed and descriptive and inferential analyses were performed. Bivariate analyses estimated the crude odds ratio. A logistic regression model was developed, and the results were presented as adjusted odds ratio. Almost half of the sample did not know the name of the drug, 20% did not know the reason for using it, 14% did not know how to use the drug, 71% declared that they were unaware of the drug’s adverse reactions, 21.3% believed that the drug did not cause any adverse reaction, and only 7.7% considered that the drug could cause some problem and 92% claimed not to have asked the doctor anything about this matter. The data show an inadequate level of HL of SUS users concerning basic information about the prescribed drug and a potential risk arising from the drug’s misuse, considering the patient’s lack of familiarity with the medication and their pathology and poor interaction with the health professional.